ChemInform Abstract: Synthesis of 2‐Aryl‐3‐trifluoromethylquinolines Using (E)‐Trimethyl(3, 3, 3‐trifluoroprop‐1‐enyl)silane. Issue 48 (26th November 2013) - Omote, Masaaki; Tanaka, Miyuu; Tanaka, Miki; Ikeda, Akari; Tarui, Atsushi; Sato, Kazuyuki; Ando, Akira
Abstract The cyclocondensation reaction to yield quinolines (V) is only suitable for aromatic aldehydes (IV), but not aliphatic aldehydes.